Rectal administration of a chlamydial subunit vaccine protects against genital infection and upper reproductive tract pathology in mice - Pais, Roshan (PLoS One, 2017)
In this study, we tested the hypothesis that rectal immunization with a VCG-based chlamydial vaccine would cross-protect mice against heterologous genital Chlamydia trachomatis infection and Chlamydia-induced upper genital tract pathologies in mice. Female mice were immunized with a C. trachomatis serovar D-derived subunit vaccine or control or live serovar D elementary bodies (EBs) and the antigen-specific mucosal and systemic immune responses were characterized. Vaccine efficacy was determined by evaluating the intensity and duration of genital chlamydial shedding following intravaginal challenge with live serovar E chlamydiae. Protection against upper genital tract pathology was determined by assessing infertility and tubal inflammation. Rectal immunization elicited high levels of chlamydial-specific IFN-gamma-producing CD4 T cells and humoral immune responses in mucosal and systemic tissues. The elicited immune effectors cross-reacted with the serovar E chlamydial antigen and reduced the length and intensity of genital chlamydial shedding. Furthermore, immunization with the VCG-vaccine but not the rVCG-gD2 control reduced the incidence of tubal inflammation and protected mice against Chlamydia-induced infertility. These results highlight the potential of rectal immunization as a viable mucosal route for inducing protective immunity in the female genital tract.